Mathematical modeling of the algorithm of special points dispersion distribution for biometric identification systems - Dorosh, O. I.; Shelestak, I. M.; Kuchmiy, H. L. (Видавництво Львівської політехніки, 2012)
This paper deals with basic methods of biometric identification and considers the algorithm of dispersion distribution of the special points around their imaginary centers of gravity.
Keywords: biometric identification methods; dactyloscopy; dispersion distribution